Responsiveness of sphingosine phosphate lyase insufficiency syndrome to vitamin B6 cofactor supplementation. Issue 5 (4th May 2020) - Zhao, Piming; Liu, Isaac D.; Hodgin, Jeffrey B.; Benke, Peter I.; Selva, Jeremy; Torta, Federico; Wenk, Markus R.; Endrizzi, James A.; West, Olivia; Ou, Weixing; Tang, Emily; Goh, Denise Li‐Meng; et al.
Abstract: Sphingosine‐1‐phosphate (S1P) lyase is a vitamin B6‐dependent enzyme that degrades sphingosine‐1‐phosphate in the final step of sphingolipid metabolism. In 2017, a new inherited disorder was described caused by mutations in SGPL1, which encodes sphingosine phosphate lyase (SPL). This condition is referred to as SPL insufficiency syndrome (SPLIS) or alternatively as nephrotic syndrome type 14 (NPHS14). Patients with SPLIS exhibit lymphopenia, nephrosis, adrenal insufficiency, and/or neurological defects. No targeted therapy for SPLIS has been reported. Vitamin B6 supplementation has therapeutic activity in some genetic diseases involving B6‐dependent enzymes, a finding ascribed largely to the vitamin's chaperone function. We investigated whether B6 supplementation might have activity in SPLIS patients. We retrospectively monitored responses of disease biomarkers in patients supplemented with B6 and measured SPL activity and sphingolipids in B6‐treated patient‐derived fibroblasts. In two patients, disease biomarkers responded to B6 supplementation. S1P abundance and activity levels increased and sphingolipids decreased in response to B6. One responsive patient is homozygous for an SPL R222Q variant present in almost 30% of SPLIS patients. Molecular modeling suggests the variant distorts the dimer interface which could be overcome by cofactor supplementation. We demonstrate the first potential targeted therapy for SPLIS and suggest that 30% of SPLIS patients might respond to cofactor supplementation.